Depletion of ZBTB38 potentiates the effects of DNA demethylating agents in cancer cells via CDKN1C mRNA up-regulation. (October 2018) - Marchal, Claire; Dieuleveult, Maud; Saint-Ruf, Claude; Guinot, Nadège; Ferry, Laure; Olalla Saad, Sara; Lazarini, Mariana; Defossez, Pierre-Antoine; Miotto, Benoit
Abstract DNA methyltransferase inhibitor (DNMTi) treatments have been used for patients with myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), and have shown promising beneficial effects in some other types of cancers. Here, we demonstrate that the transcriptional repressorZBTB38 is a critical regulator of the cellular response to DNMTi. Treatments with 5-azacytidine, or its derivatives decitabine and zebularine, lead to down-regulation of ZBTB38 protein expression in cancer cells, in parallel with cellular damage. The depletion ofZBTB38 by RNA interference enhances the toxicity of DNMTi in cell lines from leukemia and from various solid tumor types. Further we observed that inactivation ofZBTB38 causes the up-regulation ofCDKN1C mRNA, a previously described indirect target of DNMTi. We show thatCDKN1C is a key actor of DNMTi toxicity in cells lacking ZBTB38. Finally, in patients with MDS a high level ofCDKN1C mRNA expression before treatment correlates with a better clinical response to a drug regimen combining 5-azacytidine and histone deacetylase inhibitors. Collectively, our results suggest that the ZBTB38 protein is a target of DNMTi and that its depletion potentiates the toxicity of DNMT inhibitors in cancer cells, providing new opportunities to enhance the response to DNMT inhibitor therapies in patients with MDS and other cancers.